What can you expect from the Bosn J Basic Med Sci (BJBMS) in 2011? - Bakir Mehic (Biomolecules & Biomedicine, 2011)
Scientific communication has become global and almost instantaneous, and as the Editor in Chief, I feel that it is my duty to present you with the BJBMS as one of the main platforms highlighting the increasing advancements in the basic medicine.